THE STUDY OF PHYTOCHEMICAL CHANGES IN FENUGREEK LEAVES OF TWO DIFFERENT SELECTED AREAS OF GUJARAT (International Association of Biologicals and Computational Digest, 2023)
Like the majority of plants, fenugreek has a number of secondary metabolites that have significant promise. This paper’s objective is to assess the changes in phytochemicals of Unjha and Adalaj area of Gujarat using standard methods for phytochemical screening and quantitative analysis like TPC, TTC. Tannin, phenol, carbohydrates and diterpens are presented in the phytochemical screening of the both study area’s methanolic leaves extract. Unjha area’s leaf sample shows the more TPC and TTC. Thin layer chromatography for both the study area’s leaf sample was also evaluated.